PENINGKATAN VENTILASI PARU SELAMA LATIHAN FISIK DAN PENINGKATAN VO2MAX AKIBAT LATIHAN FISIK - YULIASTRID, DITA (Ilmu Keolahragaan, 2010)
Abstract : The respiratory system accomplishes exchange of air between the atmosphere and the lungs through the process of ventilation. Exchange of O2 and CO2 between the air in the lungs ang the blood in the pulmonary capillaries take place across the extremely thin walls of the air sacs, or alveoli. Alveolar ventilation may increase up to 20 fold during heavy exercise to keep pace with the increased demand for O2 uptake and CO2 output. It would seem logical that changes in the three chemical factors such as decreased PO2, increased PCO2 and increased H+, could account for the increase in ventilation, but there are many other factors play role in the ventilatory respons to exercise such as reflexes originating from body movements, increase in body temperature, epinephrine release and impulses from cerebral cortex. Regular aerobic exercise can improve max VO2 by making the heart and respiratory system more efficient, thereby delivering more O2 to the working muscles.   Key words : ventilation,VO2max, exercise